Are workers' commutes sensitive to changes in the labour market situation?. (May 2022) - Martín-Barroso, David; Núñez-Serrano, Juan A.; Turrión, Jaime; Velázquez, Francisco J.
Abstract: The present paper analyses the temporary stability of commuting to workplace functions in the face of changes in workers' and firms' characteristics and the local labour market conditions. To do this, we estimate commuting functions by incorporating four types of determinants: the characteristics of the workers, the jobs (or hiring firms), and the municipalities where the workers reside and work, including the unemployment rates to account for disequilibria in their respective local labour markets. After developing a simple model, we estimate these functions based on labour commuting microdata obtained from the population census of Spain for the years 2001 and 2011, periods with important changes in the labour market situation. We estimate commuting functions by means of ordered probit functions. The results show that the duration of commutes has not changed drastically. Additionally, most of the incorporated determinants maintain their sign and change their intensity only slightly over time. The duration of commutes is greater in the case of men, singles, educated and foreign workers, living in rented housing, using public transport, living or working in large cities, and working in large firms. In the same way, commutes are longer when the worker's municipality of residence has a high unemployment rate, and they turn out to be shorter when the municipality of the workplace has a low unemployment rate. Finally, the changes in the unemployment rate, especially in the municipality of residence, have been compensated by variation in their respective parameters, consequently offsetting their effects on commute times.